Transparency Principle on Land Acquisition for Agrarian Justice - Rosmidah Rosmidah; Dony Yusra Pebrianto (Jambe Law Journal, 2020)
The purpose of this article is to study the state’s efforts to guarantee the principle of transparency and implement it into land acquisition process for the sake of public interest. With normative method, this article found that the land, despite of being an object of private ownership, has a social function. Therefore, the state has an authority to regulate the utilisation and use of land for the sake of public interests through a land acquisition. In recent years, disputes due to land acquisition between the government and the land owners has always increased, resulting in the use of violence and public distrust against the government. It is believed that such the condition was triggered by the lack of transparency as long as the land acquisitions are concerned. In order to realize agrarian justice, which is the state’s obligation, it is necessary to guarantee the principle of transparency in the land acquisition process which are the basic rights of land owners / holders and the general public. Because the principles of openness and transparency in the Land Acquisition Law are obscure in norms, it is necessary to interpret the law. The principles of openness and transparency are carried out from the planning, preparation, implementation stages to the stage of submitting the results of land acquisition. At the empirical level, it must be implemented without causing various encapsulation resulting in land acquisition disputes. The principles of openness and transparency are needed to facilitate the flow of community participation in development